Effects of lumbar drainage on CSF dynamics in subarachnoid hemorrhage condition: A computational study - Abolfazli, Ehsan; Fatouraee, Nasser; Seddighi, Amir Saeed (Computers in biology and medicine, 2016)
Lumbar drainage is considered a therapeutic measure in treatment of subarachnoid hemorrhage. However, the evidence on the effectiveness of this method is still inconclusive. In this study, a subject-specific three dimensional model of the cerebrospinal fluid (CSF) pathways and compartments was developed. The ventricular and the cranial and spinal subarachnoid spaces were reconstructed using magnetic resonance images. Occurrence of subarachnoid hemorrhage was modeled. Since the presence of blood in the CSF spaces is known to be the cause of complications such as cerebral vasospasm, concentration of blood in these spaces was investigated. Two cases of lumbar drains that were different in the drainage rate were studied. Temporal variations of concentration of blood in CSF spaces were calculated. It was observed that lumbar drainage accelerates the clearance of blood and, thereby, the spasmogens present in the cranial and spinal subarachnoid space. Higher clearance rates were observed at higher drainage rates. •Temporal variations of blood concentration in CSF spaces following ASAH were obtained.•Lumbar drainage effectively contributed to the clearance of blood from CSF spaces.•Transmural pressure in the brain was found to decreased following administration of LD.